Personal branding on social media - The characteristics of strong personal brands in Finland - Nieminen, Lauri (My University, 2016)
The purpose of the study is to define the characteristics of strong personal brands on social media in Finland. Personal branding as a phenomenon is no longer limited to celebrities and political leaders. The digital revolution and the change in online behavior have created the need for a deeper investigation of the characteristics of strong personal brands on social media. The work of different academics on personal branding are examined to gain a comprehensive understanding on this research topic that has gone through a revolution during the last decade. Early impression management theory is refined to include elements from more modern literature related to personal branding, brand identity management and social media to create a theoretical framework that simplifies the process of personal brand building on social media. The framework consisting of three phases clarifies the process of modern personal branding. The results of the study are presented in line with three research themes derived from the theoretical framework: the background of the brand, the brand identity management and the social media behavior and activities. Mixed methods are used in the research as means to broaden perception on the subject. The quantitative part of the study defines general characteristics concerning the most follower personal brands in Finland in three social media channels – Facebook, Instagram and Twitter. The other part of the research was conducted by single case study including two Finnish personal brands cases to provide a deeper understanding of personal branding practices of strong social media personal brands. The results of the study show that the most used social media channels differ in terms of the personal brand characteristics and personal branding activities. Due to the characteristics of the channels also the post activities of the personal brands differ quite significantly. It can be also inferred that there is a difference between brands with an existing offline awareness and the brands with no awareness before joining the social media. In order to reduce the gap between the ideal brand image and the current image, the brand should have a clear vision as well as a good understanding of the target group and the value it creates for its target audience. The brand identity needs to be managed by communicating with the target audience authentically in the right channels, with relevant content. The dedication, the target group’s behavior and the ability to create valuable and relevant content determines the right tactics for social media personal branding.